Study of the association between lesion location and post-stroke depression - أمانة راما; عيسى لايقة; غياث ربيع (Latakia University Journal -Medical Sciences Series, 2023)
Background : Post-stroke depression (PSD) is a common stroke sequel . It is an independent predictor of poor prognosis for stroke, and The relationship between post-stroke depression and lesion location is controversial. Aim: The aim of this study is to evaluate the relationship between lesion location and post-stroke depression. Materials and Methods: This is a Observational prospective cohort study involved 50 patients with proven diagnosis of stroke admitted at the Department of Neurology, Tishreen University Hospital, Lattakia, during the period between September 2021- August 2022 .Patients were divided into two groups: the first group included those with PSD (18 patients). The second group included patients without PSD (32 patients). Results and discussion: Out of 50 patients, 28 were male and 22 were female, with mean age of the patients was 61.48 ± 10.6 . Frequency of PSD after 2 months was 36%. 10% of the sample had severe depression. Anxious depression was the most frequent and was found in 38.9%. There were no significant differences between the two groups regarding of age, sex, hypertension, living alone, or smoking. There were significant differences between two groups regarding of the lesion location in the frontal lobe (P-value: 0.001, Odds Ratio: 8.8),right-sided Lesion (P-value: 0.02, Odds Ratio: 3.8), and ischemic stroke (P-value: 0.01, Odds Ratio: 3.1). PSD was associated with increased disability after 2 months. Characteristics of the stroke were not associated with the severity or type of PSD or presence of suicidal thoughts. Conclusion: The current study shows that lesion in the frontal lobe, right hemisphere, and with ischemic type predict PSD, which helps to early detection and treatment as well as prevention of PSD.